Pengelolaan Feses Ayam Kampung yang Dibudidayakan di Pekarangan Sebagai Pupuk Organik Tanaman Sayur di Kelurahan Anggalomelai Kecamatan Abeli - Saili, Takdir; Nafiu, La Ode; Abadi, Musram; Libriani, Restu; Sulfitrana, Andini; Salido, Wa Laili; Isnaeni, Purnaning Dhian (Vokasi Universitas Halu Oleo, 2020)
One of chicken farming byproduct that has potential to be processed to become more economical product is manure. If not treated well, the manure could spread odour and become the media for parasitic vectors like flies. Chicken manure can be processed into organic fertilizer for vegetable farming. Aside from personal use, the organic fertilizer then can be sold and increase the farmers’ income especially in COVID-19 pandemic where most economical sector collapsed. The problem faced by farmers at Anggalomelai, Abeli sub-district was their lack of knowledge on manure processing technologies. This themed KKN Program by FPt UHO aimed to offer solutions for farmers by giving technical guidance and counseling on manure processing technologies. This program was held for one month starting from June 13th until July 13th, 2020 on Anggomelai, Abeli sub-district, Kendari. The program was carried by technical guidance and counseling for farmers, either face to face or online by still maintaining the COVID-19 prevention protocols. Result obtained from this program showed the increasing knowledge of farmers in Anggomelai, Abeli sub-district especially in prrocessing chicken manure into organic fertilizer for vegetable farming.